Efficiency of food products with zinc required to control zinc deficiency disorders - Polumbryk, Maksim; Kravchenko, Victor; Kirkova, Marina (My University, 2013)
Zinc is widely used in human body enzyme synthesis with regard to small size of its ion and ability to readily complex with ligands. Zinc deficiency disorders are widespread in several developing countries.
Keywords: дефіцит цинку; порушення обміну речовин; цинк-ферменти; фортифікації продуктів харчування; цинковмісні комплекси; дефицит цинка; нарушения обмена веществ; цинк-ферменты; фортификации продуктов питания; цинксодержащее комплексы; zinc deficiency; metabolic disorders; zinc metalloenzymes; food fortification; zinc-containing complexes; кафедра екології та екоменеджменту; кафедра харчової хімії